Sebepojetí současných českých sportovních novinářů - Chladová, Marta (Univerzita Karlova, Fakulta sociálních věd, 2024)
The profession of sports journalists, according to the literature, is in various ways outside the standards of journalistic practice. The content, form and importance of their work is often questioned. Sports editorial offices tend to work according to rules that are not typical of the rest of the media; they operate in a 'world of their own'. This dissertation reveals how sports journalists themselves perceive their profession. The qualitative research, based on in-depth interviews with former and active sports journalists from different types of media, describes their work in general terms and highlights the unique features of the profession that might enlighten their position in the journalistic hierarchy and identify any specifics that the journalists themselves perceive as relevant. The grounded theory method has been used for the analysis, through which the thesis defines the central and other major themes that resonate in and out of academia and co-create the image of sports journalists. The main aim of the research is to answer the question what the professional self-concept of Czech sports journalists is. The dissertation is a summary of findings concerning the everyday life of Czech sports journalists, with an emphasis on the characteristics of the key specifics of their profession and. Profese sportovních novinářů se podle odborné literatury v různých směrech vymyká standardům žurnalistické praxe. Obsah, forma a důležitost jejich práce bývá zpochybňována. Sportovní redakce často pracují podle pravidel, jež nejsou typická pro zbytek daného média, fungují ve "vlastním světě". Disertační práce ukazuje, jak svou profesi vnímají sami sportovní novináři a novinářky. Kvalitativní výzkum založený na hloubkových rozhovorech s bývalými i aktivními sportovními novináři z různých typů médií obecně popisuje jejich práci a akcentuje výjimečné rysy profese, jež by mohly objasnit jejich postavení v žurnalistické hierarchii a odhalit případná specifika, která sami žurnalisté vnímají jako relevantní. Pro analýzu byla ...